Diversity of Ants (Hymenoptera, Formicidae) in Two Forest Sites from Kabylia of Djurdjura, Northern Algeria - Sid-Ali, Sadou; Ali-Ahmed Djamila, Sadoudi; Ali-Ahmed Fatiha, Metna; Ouiza, Ourrad; Said, Slimani (Sociobiology, 2021)
The current study deals with the diversity of ants (Hymenoptera, Formicidae) in Kabylia of Djurdjura. It has been carried out in two forest sites from the localities of Azeffoun and Assi-Youcef, Tizi Ouzou (northern Algeria). Two sampling methods were adopted: manual capture and pitfall traps. Various community metrics were used as key elements to assess ant biodiversity within the two study sites. They included the species richness, the relative abundance, the constancy, and the Shannon-Weaver and equitability indices. Our inventory allowed identifying 24 species belonging to 12 genera and three subfamilies, which are the Myrmicinae (58%), the Formicinae (34%), and the Dolichoderinae (08%). The highest species richness was registered for the two first subfamilies, while the subfamily Dolichoderinae dominated numerically. The Site of Azeffoun, which is more submitted to human activities, recorded higher values in the number of individuals, the species richness, and the Shannon-Weaver diversity index. However, the difference between the two sites consisted mainly of the rare species, such as Crematogaster laestrygon, Goniomma sp. and Palagiolepis sp., which were present in the Azeffoun site. The local site conditions certainly have played a key role in ant species occurrence within the two study areas. Azeffoun is more disturbed than Assi-Youcef, resulting in the recruitment of much more rare and accidental species in the first site. In contrast, the rate of accessory to omnipresent species is substantially higher in Assi-Youcef, which recorded a high species evenness. To the best of our knowledge, this is the first study to report the ant genus Formica in Kabylia of Djurdjura.